2022
DOI: 10.1186/s13048-022-01034-9
|View full text |Cite
|
Sign up to set email alerts
|

UBE2T regulates epithelial–mesenchymal transition through the PI3K-AKT pathway and plays a carcinogenic role in ovarian cancer

Abstract: Background Ubiquitin-binding enzyme E2T (UBE2T), a member of the E2 family of the ubiquitin–proteasome pathway, is associated with tumorigenesis of varioustumours; however, its role and mechanism in ovarian cancer remain unclear. Results Our study revealed that UBE2T is highly expressed in ovarian cancer; this high expression was closely related to poor prognosis. Immunohistochemistry was used to validate the high expression of UBE2T in ovarian can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…It is critical for the initiation and progression of pancreatic cancer (Zheng et al, 2020) and has been demonstrated to promote the proliferation of renal cell carcinoma cells through regulating phosphoinositide 3‐kinase (PI3K)/protein kinase B (AKT) signaling (Hao et al, 2019). Suppression of UBE2T activity has also exhibited an inhibitory effect on the proliferation and invasion of ovarian cancer cells (Cui et al, 2022), lung adenocarcinoma (Li et al, 2022), and other cancers (Liu et al, 2017). Finally, UBE2T also plays important roles in primary cellular processes and participates in protein–protein interactions (Hodson et al, 2014; Lim et al, 2016; Longerich et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is critical for the initiation and progression of pancreatic cancer (Zheng et al, 2020) and has been demonstrated to promote the proliferation of renal cell carcinoma cells through regulating phosphoinositide 3‐kinase (PI3K)/protein kinase B (AKT) signaling (Hao et al, 2019). Suppression of UBE2T activity has also exhibited an inhibitory effect on the proliferation and invasion of ovarian cancer cells (Cui et al, 2022), lung adenocarcinoma (Li et al, 2022), and other cancers (Liu et al, 2017). Finally, UBE2T also plays important roles in primary cellular processes and participates in protein–protein interactions (Hodson et al, 2014; Lim et al, 2016; Longerich et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“… 10–14 UBE2T facilitates the occurrence and development of ovarian cancer by regulating epithelial–mesenchymal transition (EMT) through the PI3K-AKT pathway. 15 Further, silencing of UBE2T represses lung adenocarcinoma progression by increasing the expression of fibulin 5, 16 and UBE2T can also promote pyrimidine metabolism by enhancing Akt K63-linked ubiquitination, thus contributing to hepatocellular carcinoma (HCC) development. 17 …”
Section: Introductionmentioning
confidence: 99%